On the border discourse - Donec, P. N. (Cognition, Communication, Discourse, 2018)
The article deals with the reasons of increasingly growing interest to the subject matter of “border”. The structure of the border concept is determined. The category of “border discourse” embracing respective procedure participants’ communication and other interaction before, during and after crossing the state border is introduced; its basic features are described.